The Role of Ergonomic and Human Factors in Sustainable Manufacturing: A Review - Bassam Hasanain (Machines, 2024)
The study and implementation of ergonomics are vital for the growth of industries and improvement in work cultures. Sustainable manufacturing cannot be achieved without the implementation of human-factor ergonomics. Ergonomics is used to analyze the link between research studies and industrial practices in order to maximize the efficiency of processes by keeping in view the well-being of workforce. Designing tools, tasks, machines, systems, jobs, and settings for efficient, safe, and successful human usage involves applying knowledge about human behavior, abilities, and limitations. Workers are the backbone of the manufacturing economy. The review outlines significant advancements in preventing ergonomic problems during the design stage of the manufacturing process to achieve sustainability. The bibliometric analysis is used to identify the literature base for ergonomics. To maximize the benefits of ergonomics and to integrate sustainable practices, various methods are required to organize existing processes and technologies. The human-centered design identifies problems and aligns the output with the intended objectives of sustainability. The goal of human factors and ergonomics is to successfully integrate people into systems and develop the manufacturing processes around the well-being of workers and sustainability principles. Similarly, ergoecology, eco-ergonomics, and green ergonomics are frequently used for sustainable manufacturing. Achieving sustainability in manufacturing is not possible without considering human ergonomics. Ergonomists frequently research management, planning, and other topics to increase the efficiency of the manufacturing process. Efficient worker performance and quality of life can be enhanced through work design, management, and organizational ergonomics. Human ergonomics relates sustainability with cognitive variables such as situational awareness, human reliability, and decision-making abilities. This review explains the role of human factors and ergonomics for sustainable manufacturing.